2022
DOI: 10.1039/d1cp04152e
|View full text |Cite
|
Sign up to set email alerts
|

Activation of CO2 and CH4 on MgO surfaces: mechanistic insights from first-principles theory

Abstract: One of the most challenging topics in heterogeneous catalysis is conversion of CH4 to higher hydrocarbons. Direct conversion of CH4 to ethylene can be achieved via the oxidative coupling of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…The MgO(100) surface has the lowest surface energy among the four MgO surfaces considered here and hence is the most stable and dominant surface of the rocksalt crystals of MgO. 35 Fig. 1 describes the change in the adsorption energy of CO 2 on the (001) surface with respect to the AEEF.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The MgO(100) surface has the lowest surface energy among the four MgO surfaces considered here and hence is the most stable and dominant surface of the rocksalt crystals of MgO. 35 Fig. 1 describes the change in the adsorption energy of CO 2 on the (001) surface with respect to the AEEF.…”
Section: Resultsmentioning
confidence: 99%
“…MgO has been recognized as a prototypical basic oxide material for CO 2 capture and storage, mostly due to the abundance of MgO in nature. 34,35 Moreover, due to the presence of the various crystallographic orientations that can be differentiated based on the polarity of the surfaces, MgO can play an important role in its reactivity towards CO 2 . [36][37][38][39][40][41][42][43] In a recent computational study, Manae et al showed that CO 2 interactions with various MgO surfaces depend on the local electronic and structural properties of the active site.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, strong activation may lead to cleavage of the O 2 bond, leading to complete reduction of O 2 , yielding H 2 O. Further, strong adsorption energies may also lead to poisoning of the active sites by O 2 molecules and cause surface reconstruction, which would hinder repeated use of the catalyst . Adsorption energies in this work are calculated using normalΔ E normala normald normals = E normals normalu normalr normalf normala normalc normale + normala normald normals normalo normalr normalb normala normalt normale ( E s u r f a c e + E a d s o r b a t e ) where E surface+adsorbate , E surface , and E adsorbate are the energies of the surface–adsorbate complex, the optimized surface, and an isolated adsorbate molecule, and the negative value of Δ E ads points to a stabilizing interaction.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, strong activation may lead to cleavage of the O 2 bond, leading to complete reduction of O 2 , yielding H 2 O. Further, strong adsorption energies may also lead to poisoning of the active sites by O 2 molecules and cause surface reconstruction, which would hinder repeated use of the catalyst 53. Adsorption energies in this work are calculated using…”
mentioning
confidence: 99%